Pentacoordinated spirophosphoranide as Lewis base to activate CO2 combining with alkyl halide under mild conditions. (7th May 2022) - Wang, Di; Guo, Shanqi; Wang, Yanyan; Liu, Qiangqiang; Sun, Can; Guo, Yanchun; Zhao, Yufen; Cao, Shuxia
Abstract: A transition metal-free method to activate CO2 by pentacoordinated spirophosphoranide that acts as Lewis base at room temperature and under atmospheric pressure is reported. The reaction of hydrospirophosphorane, CO2 and alkyl halide could perform smoothly under mild conditions, and the product with a pentacoordinated P–C(O)–O–C unit could be obtained. The stereochemical mechanism was proposed by 31 P NMR tracking experiment, ESI-MS/MS tracking experiment, X-Ray analysis and DFT calculations. The reaction was presumed to proceed via a spoirophosphoranecarboxylate anion intermediate, and the phosphorus configuration was maintained throughout the reaction. The results show that pentacoordinated hydrospirophosphorane is a potential skeleton to capture and activate CO2, and can be used to establish a novel utility of CO2 in organic synthesis. Graphical abstract: Image 1